2020
DOI: 10.1002/zaac.201900202
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Velocity Assessment of Energetic Cocrystals Using QSPR Approach

Abstract: In order to design a new energetic material with desirable performance, it is necessary to know its detonation performance. This study, exhibits a linear relationship between detonation velocity of energetic cocrystals and their molecular structure through quantitative structure property relationship (QSPR) method. The methodology of this research affords a new model which can relate the detonation velocity of energetic cocrystals to their several molecular structural descriptors. Moreover, this method suppose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…The results demonstrated that the detonation properties of HMX was improved. Also, for more confidence the detonation velocity of BTNEN/HMX cocrystal was predicted through another model [22]. The detonation velocity of BTNEN/HMX cocrystal by the new model was predicted as 9.34 km.s −1 .…”
Section: Resultsmentioning
confidence: 94%
“…The results demonstrated that the detonation properties of HMX was improved. Also, for more confidence the detonation velocity of BTNEN/HMX cocrystal was predicted through another model [22]. The detonation velocity of BTNEN/HMX cocrystal by the new model was predicted as 9.34 km.s −1 .…”
Section: Resultsmentioning
confidence: 94%
“…Various approaches are available for determining the descriptors in HTC, for example, the empirical selection and algorithmic description methods [83–85] . The empirical selection methods seem to be predominantly used for descriptors selection.…”
Section: Advances In Htc Techniquesmentioning
confidence: 99%
“…( net/products_dragon.php) [50] . 为了得出爆速与高能共晶 体分子结构之间的最佳关系, Zohari和Mohammadkhani [23] 使用Dragon计算分子描述符, 并选择了多达488个 不同类型的分子描述符. Joudaki和Shafiei [40] 使用Dra-gon计算了环烷烃化合物数据集中每种化合物的1502 个理论描述符.…”
unclassified